-
If a + b + c = 1 then b + c c + a a + b a2 + b2 + c2 = ? b + c c + a a + b
-
- 1
- –1
- 0
- 2
Correct Option: C
= 1 − | − | |||
b + c | c + a | a + b |
∴ | = a − | − | |||
b + c | c + a | a + b |
= 1 − | − | |||
a + c | b + c | a + b |
∴ | = b − | − | |||
a + c | b + c | a + b |
= 1 − | − | |||
a + b | b + c | c + a |
∴ | = c − | − | |||
a + c | b + c | c + a |
∴ | + | + | |||
b + c | a + c | a + b |
= a + b + c – | ![]() | + | ![]() | – | ![]() | + | ![]() | – | ![]() | + | ![]() | ||||||
c + a | c + a | a + b | a + b | b + c | b + c |
= a + b + c – b | ![]() | ![]() | – c | ![]() | ![]() | – a | ![]() | ![]() | |||
c + a | a + b | b + c |
= a + b + c – b – c – a = 0